Determinant factors that enhancing young investor to invest in ASNB Unit Trust / Nurul Uyun Abd Talib - Abd Talib, Nurul Uyun (2010)
The purpose of this study is to determined factors enhancing young investor to invest in ASNB unit trust and refine the theoretical framework to create interest with promotion, exposure and knowledge and lastly perceive and buying behavior. A descriptive research design was adopted for this study. An extensive and critical review of literature related to create interest towards youngsters to invest in their products led to the identification of two research questions. A structured questionnaire was developed and administered to youngsters focusing on Gen Y whereby their age are between years 1983 to 1995. From the SPSS analysis, it indicates that there are positive relationships between customers exposed towards promotional strategies, customer knowledge, and customer perceive and buying behavior towards purchase unit trust fund. These results were established through crosstabs analysis. The respondents were working in Unit Trust Fund Management Company, and as such, the socio-economic background of the respondents may not be representative of consumer‟s purchase behavior generally. This paper has identified a relationship between promotion, exposure and knowledge and lastly perceive and buying behavior towards youngsters. This information should benefit practitioners and researchers alike.